Breaking the cycle the effects of different parenting styles on the intergenerational transmission of intimate partner violence - Santiago, David A.; Verbo, Allen John V.
Most studies on the intergenerational transmission of violence do not examine the role of parenting styles as mechanisms. This study explores the effects of parenting styles and other possible determinants of the intergenerational transmission of violence. This study uses data from the Cebu Longitudinal Health and Nutritional Survey (CLHNS). The study uses a final sample of n = 440 index children in Cebu, Philippines. We use information pertaining to: (1) partnership characteristics, (2) individual and intergenerational characteristics, (3) parenting styles, and (4) maternal and household characteristics. We employ logistic and multinomial logistic regression to examine the risk factors for physical violence, verbal violence, and controlling behavior in current partnerships during the past 12 months. Having an authoritative father is associated with a decreased likelihood of verbal violence in the current partnerships. Respondents who considered their mother responsible for their upbringing (RRR = 0.17), respondents who considered their father responsible for their upbringing (RRR = 0.13), and respondents who considered both parents responsible for their upbringing (RRR = 0.15) are independently associated with a decreased risk of perpetrating verbally violent acts. Furthermore, having an authoritative father (RRR = 0.37) and having a permissive father (RRR = 0.56) are independently associated with a reduced risk of reciprocating verbally violent acts. Our study shows that having an authoritative father decreases the likelihood of verbal violence in partnerships. Moreover, having an authoritative or permissive father reduces the likelihood of reciprocating verbal violence. In addition, the importance of the parent’s presence in their child’s upbringing decreases the likelihood of perpetrating verbal violence. These results suggest different interventions to prevent intimate partner violence perpetration and victimization effectively.